Proof of Concept: First Pediatric [(14)C]microtracer Study to Create Metabolite Profiles of Midazolam - van Groen, Bianca D. (Clin Pharmacol Ther, 2020)
Growth and development affect drug‐metabolizing enzyme activity thus could alter the metabolic profile of a drug. Traditional studies to create metabolite profiles and study the routes of excretion are unethical in children due to the high radioactive burden. To overcome this challenge, we aimed to show the feasibility of an absorption, distribution, metabolism, and excretion (ADME) study using a [(14)C]midazolam microtracer as proof of concept in children. Twelve stable, critically ill children received an oral [(14)C]midazolam microtracer (20 ng/kg; 60 Bq/kg) while receiving intravenous therapeutic midazolam. Blood was sampled up to 24 hours after dosing. A time‐averaged plasma pool per patient was prepared reflecting the mean area under the curve plasma level, and subsequently one pool for each age group (0–1 month, 1–6 months, 0.5–2 years, and 2–6 years). For each pool [(14)C]levels were quantified by accelerator mass spectrometry, and metabolites identified by high resolution mass spectrometry. Urine and feces (n = 4) were collected up to 72 hours. The approach resulted in sufficient sensitivity to quantify individual metabolites in chromatograms. [(14)C]1‐OH‐midazolam‐glucuronide was most abundant in all but one age group, followed by unchanged [(14)C]midazolam and [(14)C]1‐OH‐midazolam. The small proportion of unspecified metabolites most probably includes [(14)C]midazolam‐glucuronide and [(14)C]4‐OH‐midazolam. Excretion was mainly in urine; the total recovery in urine and feces was 77–94%. This first pediatric pilot study makes clear that using a [(14)C]midazolam microtracer is feasible and safe to generate metabolite profiles and study recovery in children. This approach is promising for first‐in‐child studies to delineate age‐related variation in drug metabolite profiles.